Auto-Induced Downlink Radiofrequency Electromagnetic Field Exposure at 3.5 GHz With Focusing Near the Head - Hanne Herssens; Arno Thielens (IEEE Access)
The auto-induced downlink exposure at 3.5 GHz is evaluated in networks where the power density is focused at the user equipment (UE), leading to a highly localized exposure. To achieve this focusing, various precoding techniques can be applied. Two of these are compared using Finite-Difference Time-Domain simulations. For each technique, three different exposure scenarios are considered: UE located next to the ear (phone call), UE located in front of the eyes, and the nose (video call). The exposure is evaluated in terms of the localized specific absorption rate using a female and a male phantom. We find that the exposure highly depends on the location of the UE and precoding technique. According to the International Commission on Non-Ionizing Radiation protection (ICNIRP)’s guidelines, this exposure should be normalized to the maximum incident power density. In this work, we suggest normalization strategies of this highly focused exposure and compare these. We show that the choice of normalization can create a situation where the ICNIRP basic restrictions can be exceeded while complying with the reference levels. This is important because compliance with the reference levels should ideally ensure compliance with the basic restrictions.